„Kommunikáció, ami összeköt” – Kommunikációs akadálymentesítés az ELTE BGGyK 9. Fogyatékosságtudományi Konferenciáján - Borbála Bányai; Renáta Lakos; Réka Eszenyi (Fogyatékosság és Társadalom)
The starting point for our study is the 9th Disability Studies Conference (The Boundless Expansiveness of WE), in which we describe three different forms of accessibility: interpreting between spoken languages, speech-to-text interpreting and graphic recording/facilitating. Conference language interpretation is used to bridge the barriers between languages, visual recording is used to represent the main ideas of lectures and conversations in pictures, and speech-to-text interpreting is used to put spoken language into writing. The latter two forms of interpretation convert speech into visual signs by abandoning phonation, thus facilitating the reception of linguistic signs by switching between modalities, with or without switching between languages.